Elucidating the combined toxicity of dimethomorph and difenoconazole: Intergenerational effects on different biological processes in zebrafish - Dou Wang; Yihan Wang; Liangang Mao; Xinju Liu; Chen Chen; Yanhua Wang; Guiling Yang (Ecotoxicology and Environmental Safety)
The widespread agricultural use of dimethomorph (DMO) and difenoconazole (DFC) leads to their frequent joint detection in aquatic environments. However, their combined transgenerational toxicological impacts remain largely unexplored. This study delved into the combined effects of DMO and DFC on zebrafish (Danio rerio) across multiple generations. Based on the 96-hour LC50 values obtained from zebrafish embryo acute toxicity tests, chronic exposure concentrations were established (DMO: 0.0114 mg/L; DFC: 0.0049 mg/L). Parental zebrafish (F0 generation) were exposed for 60 days prior to breeding, followed by a 7-day exposure of their F1 offspring to evaluate the transgenerational effects of individual and combined pesticides. F0 exposure precipitated pronounced oxidative stress, apoptosis, and dysregulation of key detoxification enzyme activities, including significant alterations in malondialdehyde (MDA), catalase (CAT), superoxide dismutase (SOD), Caspase-3, carboxylesterase (CarE), and glutathione S-transferase (GST). Intriguingly, these biochemical perturbations persisted in F1 progeny with amplified effects under continued exposure. Moreover, co-exposure elicited endocrine disruption, evidenced by elevated thyroid hormone levels (T3 and T4) and the upregulation of vtg, crh, and tshb transcripts, implicating profound dysregulation of the hypothalamic-pituitary-thyroid (HPT) axis. Our findings demonstrated that DMO and DFC induce significant toxicological effects in zebrafish, affecting both the directly exposed parental generation (F0) and their unexposed offspring (F1), offering critical insights for safeguarding aquatic biodiversity.